Differential Accumulation - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2011)
Early in 2011, we received a surprising invitation from the Financial Times Lexicon. A reader had suggested that an entry on differential accumulation be added to the Lexicon, and the online content developer asked us if we would be willing to write it. Our first thought was that this must have been a mistake. . . .
Keywords: 330; capital; capitalization; differential accumulation; finance; investment; modes of power; sabotage